CROP MANAGEMENT AND INTERGRATED FARMING - Dhananjay Kumar; Dhananjay Kumar (New Delhi Alfa, 2014)
This book will be of immense use in imparting knowledge on the basic principles of crop production and applied aspects of integrated farming systems.
Integrated Farmin Systems Agricultural Crops Organic Farming
Keywords: Integrated Farmin Systems, Agricultural Crops ,Organic Farming